Proteomics show antigen presentation processes in human immune cells after AS03‐H5N1 vaccination. Issue 12 (20th June 2017) - Galassie, Allison C.; Goll, Johannes B.; Samir, Parimal; Jensen, Travis L.; Hoek, Kristen L.; Howard, Leigh M.; Allos, Tara M.; Niu, Xinnan; Gordy, Laura E.; Creech, C. Buddy; Hill, Heather; Joyce, Sebastian; et al.
Abstract : Adjuvants enhance immunity elicited by vaccines through mechanisms that are poorly understood. Using a systems biology approach, we investigated temporal protein expression changes in five primary human immune cell populations: neutrophils, monocytes, natural killer cells, T cells, and B cells after administration of either an Adjuvant System 03 adjuvanted or unadjuvanted split‐virus H5N1 influenza vaccine. Monocytes demonstrated the strongest differential signal between vaccine groups. On day 3 post‐vaccination, several antigen presentation‐related pathways, including MHC class I‐mediated antigen processing and presentation, were enriched in monocytes and neutrophils and expression of HLA class I proteins was increased in the Adjuvant System 03 group. We identified several protein families whose proteomic responses predicted seroprotective antibody responses (>1:40 hemagglutination inhibition titer), including inflammation and oxidative stress proteins at day 1 as well as immunoproteasome subunit (PSME1 and PSME2) and HLA class I proteins at day 3 in monocytes. While comparison between temporal proteomic and transcriptomic results showed little overlap overall, enrichment of the MHC class I antigen processing and presentation pathway in monocytes and neutrophils was confirmed by both approaches.